QUESTIONING THE POSITION OF CORRUPTION OFFENSES IN THE RKUHP - Eko Nurisman (MIZAN, Jurnal Ilmu Hukum, 2022)
Including corruption offenses, particularly offenses, into the Draft Criminal Code (RKUHP) raises problems because the RKUHP is a compilation of general criminal law regulations included in one book. Such an arrangement raises questions about the position of corruption offenses, the Draft Criminal Code (RKUHP), and the legal consequences of regulating corruption offenses in the RKUHP. This article uses normative legal research with two approaches: legislation and conceptual. The legal materials used consist of primary, secondary, and tertiary legal materials. The result is that corruption offenses as particular offenses are only regulated regarding the core crimes. Meanwhile, the legal consequences of such an arrangement are uncertainty regarding the realization of the principle of lex specialis derogate legi generali.